Stromal cells from the adipose tissue-derived stromal vascular fraction and culture expanded adipose tissue-derived stromal/stem cells: a joint statement of the International Federation for Adipose Therapeutics (IFATS) and Science and the International Society for Cellular Therapy (ISCT) - BOURIN, PHILIPPE (2013)
BACKGROUND AIMS: Adipose tissue is a rich and very convenient source of cells for regenerative medicine therapeutic approaches. However, a characterization of the population of adipose-derived stromal and stem cells (ASCs) with the greatest therapeutic potential remains unclear. Under the authority of International Federation of Adipose Therapeutics and International Society for Cellular Therapy, this paper sets out to establish minimal definitions of stromal cells both as uncultured stromal vascular fraction (SVF) and as an adherent stromal/stem cells population. METHODS: Phenotypic and functional criteria for the identification of adipose-derived cells were drawn from the literature. RESULTS: In the SVF, cells are identified phenotypically by the following markers: CD45-CD235a-CD31-CD34+. Added value may be provided by both a viability marker and the following surface antigens: CD13, CD73, CD90 and CD105. The fibroblastoid colony-forming unit assay permits the evaluation of progenitor frequency in the SVF population. In culture, ASCs retain markers in common with other mesenchymal stromal/stem cells (MSCs), including CD90, CD73, CD105, and CD44 and remain negative for CD45 and CD31. They can be distinguished from bone-marrow-derived MSCs by their positivity for CD36 and negativity for CD106. The CFU-F assay is recommended to calculate population doublings capacity of ASCs. The adipocytic, chondroblastic and osteoblastic differentiation assays serve to complete the cell identification and potency assessment in conjunction with a quantitative evaluation of the differentiation either biochemically or by reverse transcription polymerase chain reaction. CONCLUSIONS: The goal of this paper is to provide initial guidance for the scientific community working with adipose-derived cells and to facilitate development of international standards based on reproducible parameters.